Carrying Concealed Weapons Prohibited, A Compilation of the Laws and Ordinances of the Corporation of Lebanon, Ch. 20 Misdemeanors, §23. - (:unkn) unknown (My University, 1871)
Whoever shall carry concealed upon or about his person any pistol, Bowie knife, dirk, sword cane or other dangerous weapon, within the limits of the Corporation, unless on a journey or permitted by law to carry weapons, shall be deemed guilty of a misdemeanor, and fined not less than three dollars nor more than fifty [dollars] for each offence."
Keywords: CARRY - CONCEALED